The Psychological Approach to Islamic Studies: Between Theory and Practice - Hopipah, Eva Nur; Kamil, Sukron; Mudzhar, M. Atho (Tasfiyah: Jurnal Pemikiran Islam, 2025)
There are different approaches to Islamic Studies, one of which is the psychological approach. This approach focuses on the psychological aspects that influence the study of Islamic Studies. In its development, the psychological approach has received various criticisms, both normative and empirical, from both classical and contemporary perspectives. This research aims to explore and develop the psychological approach in Islamic Studies more comprehensively, both theoretically and practically. The research method used is library research by analyzing various literatures. Primary sources in this research include classical and modern books and articles related to psychological approach in Islamic studies. Meanwhile, other books and articles relevant to this research are used as secondary sources. The results of this study show that there is a strong connection between theory and practice in the psychological approach in Islamic studies. However, there are also aspects that are not fully aligned between the theoretical framework and its application, both in the normative and empirical areas. The psychological approach in Islamic studies has a close relationship between theory and practice, although there are fundamental differences in understanding human psychological dynamics. Theoretically, the Islamic psychological approach is different from general psychology, while empirically, its application still faces challenges in understanding human psychological dynamics. However, this approach still offers advantages in the integration of knowledge, contextual understanding, and more comprehensive data-based analysis.